2022
DOI: 10.1080/00131881.2022.2090981
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in online classes during Covid-19: the experiences of newly-arrived migrant students

Abstract: Background:In order to continue educational provision during the COVID-19 pandemic, many education systems switched to some form of Emergency Remote Teaching (ERT) in 2020. Research suggests that this may have disproportionately affected students from underprivileged communities. In this context there is, therefore, a pressing need to consider how ERT may have impacted learners who are likely to be most affected by educational inequalities, including newly arrived migrant students (NAMS).Purpose: As studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Regardless of how the students receive the informational content, in the online environment, the process is based on the interaction with peers, teachers, and the informational content provided by them [87]. Numerous studies have investigated the obstacles faced by teachers in interacting with students in the online environment, e.g., their low technological literacy, lack of knowledge of the psychological implications of using technology in teaching, and the absence of digital resources [88,89]. The present analysis points out several positive aspects of the interaction with teachers, such as the facilities offered by technology in teaching and online communication (Zoom, virtual platform, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of how the students receive the informational content, in the online environment, the process is based on the interaction with peers, teachers, and the informational content provided by them [87]. Numerous studies have investigated the obstacles faced by teachers in interacting with students in the online environment, e.g., their low technological literacy, lack of knowledge of the psychological implications of using technology in teaching, and the absence of digital resources [88,89]. The present analysis points out several positive aspects of the interaction with teachers, such as the facilities offered by technology in teaching and online communication (Zoom, virtual platform, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Participants have fewer opportunities to communicate with the teacher, which does not support active participation. Seynhaeve et al,(2022) found that most of all, there are limited opportunities for learner-centred interaction during the online mode of instruction. However, Choi et al,(2021) assert that interaction opportunities for teachers and students are key factors of academic success.…”
Section: Discussionmentioning
confidence: 99%
“…Research on interaction in online classes highlights silence as one of the obstacles for online teaching and learning (e.g. Seynhaeve et al, 2022;Saraç & Doğan, 2022), as instructors report a tendency among students to mute themselves during online lessons. Given the increasing popularisation of online teaching platforms in the digital and post-pandemic age, it is important that more research into the interaction in online classrooms is conducted so that the nature of silence in online institutional talk can be better understood.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…However, several studies have highlighted that learner-leaner interaction is largely missing in online synchronous learning environment (e.g. Rautela et al, 2022;Seynhaeve et al, 2022;Cheung, 2023). For instance, in their study exploring migrant students' experiences of online interaction during ERT, Seynhaeve et al (2022) found that most participants reported a lack of opportunities for learner-learner interaction in online classes due to technological difficulties and the tutor's lesson design.…”
Section: Interaction In the Online Classroommentioning
confidence: 99%
See 1 more Smart Citation